2015
DOI: 10.1179/1753807615y.0000000017
|View full text |Cite
|
Sign up to set email alerts
|

The influence of adult family members on children's fast food consumption: A health belief perspective

Abstract: This study, which positions adult family members as health advocates and active promoters of their children's health, explicates the health beliefs and health actions of adult caregivers in limiting children's fast food consumption to prevent childhood obesity. Based on a survey of 124 parents, grandparents, and older siblings in Singapore, this study, which is grounded in the Health Belief Model, found that the strongest predictor of adult family members' behaviors to limit children's consumption of fast food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…The themes that emerged from the analysis to answer Research Question 2 were factors for eating healthy such as good taste, recipe availability, low cost for healthy ingredients, accessibility of the ingredients, substitutions of herbs and spices, and food waste. The results of this study confirmed the findings from Jurkowski et al 2014and Lee and Lien (2015) that the main factor that influences obese AA women to continue to prepare and consume traditional soul food is the taste. Obese AA women love and desire the rich taste of traditional soul food.…”
Section: Research Questionsupporting
confidence: 91%
“…The themes that emerged from the analysis to answer Research Question 2 were factors for eating healthy such as good taste, recipe availability, low cost for healthy ingredients, accessibility of the ingredients, substitutions of herbs and spices, and food waste. The results of this study confirmed the findings from Jurkowski et al 2014and Lee and Lien (2015) that the main factor that influences obese AA women to continue to prepare and consume traditional soul food is the taste. Obese AA women love and desire the rich taste of traditional soul food.…”
Section: Research Questionsupporting
confidence: 91%